Penguraian Zat Warna Metilen Biru Menggunakan Katalis Fe3O4-Fe2O3 Dalam Silika Mesopori - Winda Selfira; Syamsi Aini (Departemen Kimia FMIPA UNP, 2021)
Dyestuff waste from the textile industry process which is disposed of directly into the environment will cause problems because it is toxic and carcinogenic. Methylene blue is one of the azo dyes that is often used as a textile dye. One way to decompose dyes is to use a catalyst Fe3O4-Fe2O3@SiO2 which is synthesized using natural raw materials from iron sand and silica sand and is assisted by H2O2 oxidizer through the fenton method with the formation of OH for the decomposition process of methylene blue. Decomposition of methylene blue has been carried out using the fenton method using Fe3O4-Fe2O3@SiO2 as a catalyst and H2O2 as an oxidizing agent. The experimental parameters were the optimum time, the optimum amount of catalyst and the reusability test of the Fe3O4-Fe2O3@SiO2 catalyst in decomposing methylene blue. The optimum conditions for decomposition of the methylene blue dye using Fe3O4-Fe2O3@SiO2 were 60 minutes and the amount of catalyst was 100 mg. At the optimum condition, the percentage of degradation is > 98%. For testing the reusability of the Fe3O4-Fe2O3@SiO2 catalyst can be used 2x to decompose methylene blue. In the second use, the percentage of degradation is 83%, this is because Fe3O4 has changed to Fe2O3 so that the degradation result decreases.